Study on the efficacy of artemisia oil for acne and the underlying mechanisms in mice - Hu HUANG; Zhibo YANG; Ziyan QIN; Kan TAO; Huailong CHANG; Lili GUO; Zhanghua HE; Biyao MAO (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Objective To assess the effect of artemisia annua oil (AN) on skin damage and inflammation in a mouse model of acne. Methods Forty-eight mice were randomly divided into normal, model, vehicle-treated and different concentrations of AN-treated groups (0.5% AN, 1.0% AN, 1.5% AN, 3.0% AN, 5.0% AN), with 6 mice per group. Except for the normal controls, the other mice were intradermally injected with P. acnes to induce acne. When the acne model was successfully established, mice in model group were fed normally. Mice in vehicle-treated group were sprayed with 1 mL of normal saline, while AN-treated groups were sprayed with 1 mL of different concentrations of AN for 7 days. The skin condition on the back of mice was observed and the skin area of acne was measured. After the treatment, serum and skin tissue were collected. HE staining was used to observe the pathological changes in the skin. ELISA assay was used to measure the serum levels of inflammatory cytokines, including IL-6, IL-1β and TNF-α. Results Five days after injection of P. acnes, inflammatory bumps with ruptures developed on the injection site. Treatments with different concentrations of AN induced various extent of improvements in inflammation and swelling of the skin lesions. Bumps became subsided. AN at concentration of 1.5% or over exhibited a superior efficacy. In comparison to vehicle-treated controls, AN at concentrations of 0.5%, 1.5%, 3.0% or 5.0% significantly decreased the acne area (both P<0.05). However, treatments with 1.0% AN did not significantly decreased the acne area (P>0.05). In comparison to model group, treatments with AN improved skin damage and inflammation at various extent, with a more prominent effect at the concentration of 1.5%. In addition, the serum levels of IL-6, IL-1β and TNF-α were significantly higher in the model group than in the normal controls (P<0.01). However, only 1.5% of AN markedly lowered the serum levels of IL-6, IL-1β and TNF-α (P<0.01 vs. model group) although other concentrations of AN also decreased these cytokine levels. Conclusion AN has a therapeutic effect on acne in mice, possibly via inhibition of inflammatory response during the development of acne. However, further research is needed to determine optimal concentration of AN.